Value Orientations as Determinants of Preference for External and Anonymous Whistleblowing - Nayir, Dilek Zamantili; Herzig, Christian (2012)
Incidences of organizational wrongdoing have become wide spread throughout the whole business world. The management of organizational wrongdoings is of growing concern in organizations globally, since these types of acts can be detrimental to financial well being. Wrongdoing occurs within organizational settings and organizational members commonly have knowledge of and thus the opportunity to report the wrongdoing. An employee’s decision to report individual or organizational misconduct, i.e. blow the whistle, is a complex phenomenon that is based upon organizational, situational and personal factors. The purpose of this study is to examine the relationship between value orientations of individuals and choices for particular whistleblowing modes. Our results show that there are significant relationships between these variables. We contribute to the extant literature by choosing Turkey as context as most studies have been conducted in the US and Europe, and little has been reported about the actions taken by employees in non-Western cultures when they observe wrongdoing in their organizations.
Keywords: Turkey; Reporting organizational wrongdoing; Individualism/collectivism; Idealism/relativism; Value orientations of employees; Modes of whistleblowing